2003
DOI: 10.1038/sj.ijo.0802263
|View full text |Cite
|
Sign up to set email alerts
|

Rates of weight change for black and white Americans over a twenty year period

Abstract: OBJECTIVE:To examine the rate of weight gain over time among Americans by age, gender, and race. PARTICIPANTS: Scientific sample of 5117 Americans, ages 25-74 y in 1971 followed for 20 y. RESULTS: Rates of weight gain estimated by mixed effects models are highest among young adults and rates of weight loss are greatest among older adults. The overall shape of the growth curves are similar for men and women, black and white, in terms of both weight gain and weight loss. Rates are also affected by baseline body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
142
4
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(169 citation statements)
references
References 12 publications
21
142
4
1
Order By: Relevance
“…In a recent FNS study (16 years of follow-up) (29) as well as in the CARDIA study (47) , San Antonio Heart Study (49) , rural Wisconsin (50) , the Canadian Multicentre Osteoporosis Study (51) , the West of Scotland Twenty-07 Study (43) , the Melbourne Collaborative Cohort Study (52) , the HUNT Study (53) and the OsLof study (45) (follow-up: 5-11 years), younger adults likewise gained more weight. Similar to the present study, larger weight gains also occurred in normal-weight and overweight women in the previous FNS study (29) , NHANES I (48) , HUNT (53) and OsLof (45) studies as well as in overweight Australian women (52) . In the USA, younger, normal-weight and overweight African Americans generally gained more weight than their Caucasian counterparts; older African-American women, however, started losing weight earlier (fifth and sixth decades) and faster than Caucasian women (47,48) .…”
Section: Discussionsupporting
confidence: 90%
“…In a recent FNS study (16 years of follow-up) (29) as well as in the CARDIA study (47) , San Antonio Heart Study (49) , rural Wisconsin (50) , the Canadian Multicentre Osteoporosis Study (51) , the West of Scotland Twenty-07 Study (43) , the Melbourne Collaborative Cohort Study (52) , the HUNT Study (53) and the OsLof study (45) (follow-up: 5-11 years), younger adults likewise gained more weight. Similar to the present study, larger weight gains also occurred in normal-weight and overweight women in the previous FNS study (29) , NHANES I (48) , HUNT (53) and OsLof (45) studies as well as in overweight Australian women (52) . In the USA, younger, normal-weight and overweight African Americans generally gained more weight than their Caucasian counterparts; older African-American women, however, started losing weight earlier (fifth and sixth decades) and faster than Caucasian women (47,48) .…”
Section: Discussionsupporting
confidence: 90%
“…Sheehan et al quantified weight gain by race/gender strata. For each strata, they showed that weight gain was most rapid for those in their 20s, 30s, and 40s and then tended to level off and then decrease after age 60 (7). However, neither they nor more recent growth curve or trajectory analyses by Clarke et al (4) or Østbye et al (6) provide separate estimates of likely weight trajectories by starting BMI category.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have estimated average weight gain among adults in the general population or for specific population subsets (4)(5)(6)(7). For example, in a recent and highly cited study, Mozaffarian et al (5) reported average annual weight gain of 0.38 kg (0.84 lb) among nonobese adults in the US.…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature suggests that younger adults, women and African Americans are at higher risk of gaining weight over time and becoming overweight (9)(10)(11)(12)(13)(14)(15)(16)(17) . Still, the evidence is not conclusive; there are equivocal findings (17,18) and the results may be affected by confounding parameters, such as socio-economic and marital status, changes in smoking habits and physical activity patterns, or inherent sample characteristics and longitudinal changes (19)(20)(21)(22) . Furthermore, potential 'protective' dietary components contributing to weight maintenance and prevention of weight gain have been identified, i.e.…”
mentioning
confidence: 99%